2016
DOI: 10.1519/jsc.0000000000001425
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Effects of Balance and Plyometric Training on Physical Performance in Youth Soccer Athletes

Abstract: Hammami, R, Granacher, U, Makhlouf, I, Behm, DG, and Chaouachi, A. Sequencing effects of balance and plyometric training on physical performance in youth soccer athletes. J Strength Cond Res 30(12): 3278-3289, 2016-Balance training may have a preconditioning effect on subsequent power training with youth. There are no studies examining whether the sequencing of balance and plyometric training has additional training benefits. The objective was to examine the effect of sequencing balance and plyometric training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 38 publications
8
119
1
2
Order By: Relevance
“…Many strength and conditioning coaches prescribe plyometric training sessions using fixed box heights (i.e., a 30-cm box), considering, for example, the mean countermovement jump performance of the subjects a good parameter for defining optimal dropping height (22). In fact, previous interventions adopting this method have been shown to be effective for enhancing power-related capacities in youth soccer players (13,35,44). However, with current data, we cannot determine which of the above methods is more effective and this can potentially violate the training principle of individualization.…”
Section: Introductionmentioning
confidence: 83%
“…Many strength and conditioning coaches prescribe plyometric training sessions using fixed box heights (i.e., a 30-cm box), considering, for example, the mean countermovement jump performance of the subjects a good parameter for defining optimal dropping height (22). In fact, previous interventions adopting this method have been shown to be effective for enhancing power-related capacities in youth soccer players (13,35,44). However, with current data, we cannot determine which of the above methods is more effective and this can potentially violate the training principle of individualization.…”
Section: Introductionmentioning
confidence: 83%
“…Thus, plyometric training activities are positively augmented with greater balance or postural control. For example, when 4 weeks of balance training was incorporated prior to 4 weeks of plyometric training the training outcomes were significantly better with youth than in the reverse order (Hammami et al, 2016b). Hence, the combination of inadequate strength and balance would inhibit positive sprint training adaptations associated with plyometric training with youth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, resistance training for youth should initially emphasize strength training methods. Prior research has also demonstrated the importance of introducing balance training early in the training process (Behm et al, 2008; Hammami et al, 2016b). Plyometric training can also be included but this training should emphasize lower amplitude movements with low to moderate reaction forces (Behm et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As the result of their study, they found that there were significant differences between players' speed and agility skills pre-test and the post-test scores of the experimental group (p=0,000). Hammami et al, (2016) [24], determined that 8-week studies with 4 weeks balance and 4 weeks of plyometric exercises on elite players aged 12-13, have improved sprint acceleration and balance. Chaouachi et al, (2014) [25], determined a significant improvement in 10 m sprint times of 12-15 years male adolescents after 8 weeks of a combined balance and plyometric training program.…”
Section: Discussionmentioning
confidence: 99%